Advancements on bifurcation behavior and operational deflection shapes of disk brake creep groan. (15th September 2022) - Huemer-Kals, Severin; Kappauf, Jonas; Zacharczuk, Martin; Hetzler, Hartmut; Häsler, Karl; Fischer, Peter
Abstract: Disk brake creep groan vibrations are friction-induced stick–slip vibrations. Their impulse-like excitation, caused by the physical properties of the frictional contacts, leads to strongly nonlinear vibrations of brake system, axle and also chassis parts. As with many nonlinear phenomena, theoretical and experimental investigations on the bifurcation behavior were already done. So-far performed experiments used either strongly reduced setups or were limited in the controllability of testing, leading to certain deviations and a reduced complexity compared to the real-world behavior of the full vehicle. In this work, an approach based on half-axle tests is presented. Here, tire and rim are part of the system. By running drum-driven test matrices, extended stability maps of the rest position were created. An operational deflection shape (ODS) analysis over all 72 operating points of the test matrix was performed. Together with the relative speeds in the friction contact, a novel classification of creep groan phenomena is presented. These results prove an interaction between longitudinal and rotational axle displacements during creep groan, which was already assumed in corresponding vehicle tests. The insights enable a clearer distinction of creep groan, which is necessary for the accurate objective rating of creep groan phenomena in industry. Furthermore, the ODS results suggest the structure for a sufficient minimal model. Highlights: Longitudinal axle and rotational wheel carrier vibrations interact during creep groan. Tire and rim are necessary to include longitudinal vibration effects. With tire and rim, five instead of three creep groan bifurcation zones were found. The structure of a 3-DOF minimal model for creep groan's main effects is presented.